A dynamic Ellsberg urn experiment - Dominiak, Adam; Duersch, Peter; Lefort, Jean-Philippe (Games and economic behavior, 2012)
Many theories of updating under ambiguity assume either dynamic consistency or consequentialism to underpin behaviorally the link between conditional and unconditional preferences. To test the descriptive validity of these rationality concepts, we conduct a dynamic extension of Ellsbergʼs 3-color experiment. We find that more subjects act in line with consequentialism than with dynamic consistency and that this result is even stronger among ambiguity averse subjects. ► We experimentally test consequentialism versus dynamic consistency. ► The design is a dynamic extension of the 3-color Ellsberg urn. ► More subjects violate dynamic consistency than consequentialism. ► Violating subjects (for both axioms) are less confident in their responses.